2020
DOI: 10.3126/nje.v10i3.28397
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of tuberculosis patient of Samtse General Hospital, Bhutan

Abstract: Background: Tuberculosis (TB) is one of the major public health problems in Bhutan. Evaluation of treatment outcomes of TB and identification of the risk factors are important components for the success of National TB control program. Therefore, this study was undertaken to assess the TB treatment outcome and factors associated with it in Samtse General Hospital. Methods: This was a retrospective, cross sectional study using the TB data from Samtse General Hospital from 2008–2019. A univariate and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Studies underscore the elevated likelihood of etiologically positive PTB among farmers in China [41]. Furthermore, our study, alongside existing research, indicates a lower successful treatment rate for etiologically positive PTB compared to negative cases, as well as for retreated PTB patients compared to initial treatment [42][43][44][45].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Studies underscore the elevated likelihood of etiologically positive PTB among farmers in China [41]. Furthermore, our study, alongside existing research, indicates a lower successful treatment rate for etiologically positive PTB compared to negative cases, as well as for retreated PTB patients compared to initial treatment [42][43][44][45].…”
Section: Discussionsupporting
confidence: 58%
“…Our study revealed a commendable successful treatment rate exceeding 90% (95.77%) among PTB patients in Guizhou Province, positioning it favorably in comparison to both domestic and international counterparts [28][29][30]. However, the curative outcome for PTB in Guizhou Province remained suboptimal at 42.54%, indicating a notable disparity when juxtaposed against the 50-73% cure rates observed in other Chinese regions [31][32][33].…”
Section: Discussionmentioning
confidence: 71%
“…The mean treatment success rate of above WHO recommended cutoff of 90% (93%) in the study district is comparable to national [ 22 , 23 ] and other countries in the region including Bangladesh (94%), Nepal (91%), Sri Lanka (85%), Pakistan (93%) [ 24 ] and Ethiopia (92.5%) [ 25 ]. This is in line with the recommended target of the End TB Strategy set by the WHO [ 2 , 18 ].…”
Section: Discussionsupporting
confidence: 51%